PENGARUH PENAMBAHAN AMILUM GEWANG (Corypha utan Lamarck) SECARA INTRAGRANULAR DAN EKSTRAGRANULAR TERHADAP SIFAT FISIK TABLET PARACETAMOL DENGAN METODE GRANULASI BASAH - Maria Hilaria; Devi Ristian Octavia (Jurnal Ilmiah Manuntung, 2020)
Gewang (Corypha utan Lamk) is a member of a palm tree that grows wild in most parts of Indonesia. The gewang plant is rich in starch which is thought to be used as an additional ingredient in making Paracetamol tablets with wet granulation methods. This study aims to determine the effect of starch supplementation on the physical properties of Paracetamol tablets. This research is a type of experimental research. Tablets are made in three formulas based on variations in the ratio of starch gewang intragranular and extragranular. Comparison of three formulas intragranular and extragranular, namely: FI (100%: 0%), FII (75%: 25%), FIII (0%: 100%). Tablets are made in wet granulation method with starch binder. Homogeneous dry granules then tested for physical properties of granules include: flow time, stationary angle, and tapping. Furthermore, pressing and tablets obtained were tested for the physical and chemical properties of tablets including weight uniformity and hardness. Statistical analysis of the physical quality of tablets was carried out by the Kolmogorov-Smirnov data normality test, followed by the dendan One Way Anova. The results showed that the use of starch gewang intragranular, extragranular and intragranular and extragranular combinations affected the physical properties of tablets. The method of adding extragranular starch starch to formula 3 produced tablets with effective tablet fragility, which was to meet the physical properties of tablets.